Jet-hadron correlations with respect to the event plane in √𝑠𝑁⁢𝑁 = 200 GeV Au + Au collisions in STAR - Abdulhamid, Muhammad Ibrahim; Deppner, Ingo Martin; Herrmann, Norbert; Leung, Yue; Söhngen, Yannick (Physical review, 2024)
Angular distributions of charged particles relative to jet axes are studied in √𝑠𝑁⁢𝑁=200 GeV Au+Au collisions as a function of the jet orientation with respect to the event plane. This differential study tests the expected path-length dependence of energy loss experienced by a hard-scattered parton as it traverses the hot and dense medium formed in heavy-ion collisions. A second-order event plane is used in the analysis as an experimental estimate of the reaction plane formed by the collision impact parameter and the beam direction. Charged-particle jets with 15<𝑝T,jet<20 and 20<𝑝T,jet<40 ⁢GeV/𝑐 were reconstructed with the anti-𝑘T algorithm with radius parameter setting of 𝑅=0.4 in the 20-50% centrality bin to maximize the initial-state eccentricity of the interaction region. The reaction plane fit method is implemented to remove the flow-modulated background with better precision than prior methods. Yields and widths of jet-associated charged-hadron distributions are extracted in three angular bins between the jet axis and the event plane. The event-plane (EP) dependence is further quantified by ratios of the associated yields in different EP bins. No dependence on orientation of the jet axis with respect to the event plane is seen within the uncertainties in the kinematic regime studied. This finding is consistent with a similar experimental observation by ALICE in √𝑠𝑁⁢𝑁 = 2.76 TeV Pb-Pb collision data.
Im Titel stehen der Ausdruck "sNN" unter dem Wurzelsymbol, NN ist dabei tiefgestellt
Gesehen am 14.05.2025